The new labor systems in the economy of the precariat. The case of deliverymen through Rappi, Uber Eats and Glovo platforms - Carrión Chulluncuy, Joselyn (2020)
The neoliberal economy in its process of expansion and continuous capacity of reinvention has been adapted to the new contexts of crisis and has generated socioeconomics relations under new forms of labor relations and mechanisms of work. This is how since the last decade new forms of independent work have massively emerged, precarious jobs in the so called collaborative economy that reproduce and extend the continuous informalization and precariousness of employment in Peruvian society, now involved in the entrepreneurship speech. The aim is to analyze the new emerging labor forms in the precariat economy, all of this on the base of a case study of the delivery men of the Rappi, Uber eats and Glovo platforms. The methodology used has been qualitative, 12 in-depth interviews were conducted, the fieldwork was carried out between 2018-2019 in Lima Metropolitana.